(untitled) (Research, Society and Development, 2022)
Brazil occupies a relevant position in the production of food from agribusiness, in crops such as corn, soybeans and coffee. However, logistics is one of the biggest problems in Brazilian food production and, more specifically, grains. The objective of this work was to analyze the logistics of grain production in Brazil, which in fact influences the entire production chain. Logistics is an important activity in agribusiness and despite the difficulties encountered such as the lack of investments, it is a step that contributes to the country in terms of economy. The transport system is essential for the movement of the country’s economy, without it products would not reach consumers, industries would not have access to raw materials and would not even be able to sell their production. It is a sector that enables all other sectors. In addition, transport adds to the quality of logistics services, as it directly impacts delivery time, reliability and product safety. Choosing the mode of transport to be used is extremely important and despite agribusiness being strong in Brazil, there are still many difficulties in transporting cargo. There are several types of modes, but not all of them are used, being the road the main one. The country has the fourth largest road network in the world, but most of it is unpaved. Brazil needs planning and investment to solve the problem of the transport logistics matrix.